2020
DOI: 10.1021/acs.est.9b07852
|View full text |Cite
|
Sign up to set email alerts
|

Brown Carbon Production by Aqueous-Phase Interactions of Glyoxal and SO2

Abstract: Oxalic acid and sulfate salts are major components of aerosol particles. Here, we explore the potential for their respective precursor species, glyoxal and SO 2 , to form atmospheric brown carbon via aqueousphase reactions in a series of bulk aqueous and flow chamber aerosol experiments. In bulk aqueous solutions, UV-and visible-light-absorbing products are observed at pH 3-4 and 5-6, respectively, with small but detectable yields of hydroxyquinone and polyketone products formed, especially at pH 6. Hydroxymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…209 These results indicate that evaporation-driven BrC formation can be important in organic mixtures other than the imine BrC system. BrC formation through aqueous reactions of glyoxal and sulfite leading to organosulfates compounds has also been observed recently 210 and may indicate that these types of reactions can be important even without evaporation. While many laboratory studies have identified the formation of BrC upon droplet or bulk solution evaporation, confirmation of this process has yet to be observed in ambient cloud droplets and aerosol particles.…”
Section: Cloud and Fog Droplet Evaporation Processes Leading To Brcmentioning
confidence: 62%
See 1 more Smart Citation
“…209 These results indicate that evaporation-driven BrC formation can be important in organic mixtures other than the imine BrC system. BrC formation through aqueous reactions of glyoxal and sulfite leading to organosulfates compounds has also been observed recently 210 and may indicate that these types of reactions can be important even without evaporation. While many laboratory studies have identified the formation of BrC upon droplet or bulk solution evaporation, confirmation of this process has yet to be observed in ambient cloud droplets and aerosol particles.…”
Section: Cloud and Fog Droplet Evaporation Processes Leading To Brcmentioning
confidence: 62%
“…These results indicate that evaporation-driven BrC formation can be important in organic mixtures other than the imine BrC system. BrC formation through aqueous reactions of glyoxal and sulfite leading to organosulfate compounds has also been observed recently and may indicate that these types of reactions can be important even without evaporation.…”
Section: Aqueous and In-cloud Reactions Of Brcmentioning
confidence: 64%
“…Recently, the quantum chemical calculations by Chen and Zhao (2020) suggested that hydroxymethyl sulfite (HMSi), an isomer of HMS, might also be produced by an aqueous reaction of HCHO and SO 2 . The laboratory experiments of De Haan et al (2020) demonstrated that HMS was one of the major products from the aqueous processing of glyoxal monobisulfite (CH(OH) 2 CH(OH)SO −…”
Section: Knowledge Gained and Remaining Gapsmentioning
confidence: 99%
“…69 Other aldehydes can also react with SO 2 to produce other hydroxyalkylsulfonate species that may be atmospherically important. For example, De Haan et al 129 observed the formation of HMS, C 2 , and C 3 sulfonates from the reaction between S(IV) and glyoxal in bulk aqueous solutions and aerosol particles at atmospherically relevant pH values. 4.7.…”
Section: Laboratory Studies Of Reaction Pathways Of Current Interestmentioning
confidence: 99%